The role of angiotensin signalling in anthracycline-induced cardiotoxicity. (14th October 2021) - Findlay, S; Plummer, C J; Plummer, R; Gill, J H
Abstract: : Anthracyclines (e.g. epirubicin, doxorubicin, daunorubicin) are widely used for the treatment of adult and paediatric cancers. Despite their therapeutic efficacy, anthracyclines are associated with both acute and late-onset cardiac toxicities. Meta-analyses report an overt cardiotoxicity incidence of 6.3%, whilst sub-clinical cardiotoxicity incidence is 17.9% (1). Angiotensin converting enzyme (ACE) inhibitors are used to treat anthracycline-induced cardiotoxicity (AIC) (2) and despite their efficacy being well studied for the treatment of heart failure, hypertension and post-acute coronary syndromes, their mechanism(s) for treating and preventing AIC remain unknown. Using in vitro cardiomyocytes, we evaluated the angiotensin signalling mechanisms stimulated by doxorubicin chemotherapy, applying quantitative PCR, immunofluorescence and real-time cell analysis technologies. In vitro adult human ventricular cardiomyocytes (AC10 cell line) treated with clinically relevant sub-toxic concentrations of doxorubicin, demonstrate a dose and time-dependent increase in angiotensin II type-1 receptor (AT1R) gene expression. Maximal AT1R expression was observed after 24 hours' exposure at 250 nanomolar (nM), with qPCR recording up to 13-fold increases in expression relative to control (figure 1). Consistent with gene expression studies, doxorubicin also induced expression of AT1R at the protein level, with immunofluorescence imaging displaying up-regulation of AT1R in association with doxorubicin concentrations up to 500nM (figure 2). Western blot results also support the induction of AT1R, however no relationship was observed between either doxorubicin concentration or drug exposure time. Cellular growth and morphological changes of cardiomyocytes in response to clinically relevant doses of doxorubicin treatment were evaluated with real-time cell analysis using impedance-based xCELLigence technology. During the early phases of doxorubicin exposure, an increase in cell size was observed, whilst experiments modelling the pharmacokinetics and serial half-lives of doxorubicin demonstrated reversibility of doxorubicin-induced cardiomyocyte injury following drug elimination. These data support the mechanistic hypothesis that a relationship exists between AIC and modulation of the angiotensin signalling pathway in cardiomyocytes. We demonstrate that cardiomyocyte exposure to doxorubicin induces AT1R gene and protein expression, whilst doxorubicin-induced cardiomyocyte injury displays reversibility following drug elimination. Genetic polymorphisms within the ACE gene have been associated with cardiomyopathy and left ventricular hypertrophy. Our research now provides the platform to ascertain whether the ACE genotype contributes to heart failure from AIC, and whether an elevation in pro-hypertrophic angiotensin II levels could exacerbate anthracycline-induced hypertrophy and promote the development of late-onset anthracycline-induced heart failure. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Cancer Research UK PhD research grant